Is the association between vitamin D, adiponectin, and insulin resistance present in normal weight or obese? A pilot study. (February 2019) - Carvalho-Rassbach, Marina; Alvarez-Leite, Jacqueline Isaura; de Fátima Haueisen Sander Diniz, Maria
Summary: Objective: Obesity is classically associated with vitamin D deficiency. The aim of this study was to investigate the association of vitamin D with serum adiponectin concentration and insulin resistance in normal weight and obese individuals. Research methods and procedures: Cross-sectional analysis was performed in 76 participants without diabetes (40 obese and 36 normal weight) from a convenience sample of a health counseling center in Belo Horizonte, MG, Brazil. All participants self-reported their skin color as white. Body weight and height were used to calculate body mass index (BMI). Serum insulin, glycemia, vitamin D (25OHD), and adiponectin were evaluated after 12 h fasting. Body fat percentage by electric bioimpedance and waist circumference were analyzed. Pearson's or Spearman's correlation coefficients were calculated. Age- and gender-adjusted associations by multivariate logistic regression were used. Multiplicative interaction terms between 25OHD/adiponectin and BMI were calculated. Results: Participant's mean age was 35 ± 9.5 years; 75% were female, and 65.8% were vitamin D insufficient (25OHD < 20 ng/mL). The mean of 25OHD was 28.4 ± 8.6 ng/mL, median of adiponectin was 204 ng/L, and the median of Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) was 2.2. There was no association between 25OHD status, adiponectin, and HOMA-IR in total sample or among obese or normal weight individuals. After adjustments, there was an association between 25OHD insufficiency and body fat percentage (odds ratio = 0.94; confidence interval 95% = 0.88 to 0.99, p = 0.04) in the total sample. BMI did not influence the association between 25OHD and adiponectin. Conclusion: There was a negative association between fat percentage and 25OHD status, but there were no associations between 25OHD, adiponectin, and insulin resistance in this sample. Further studies are needed to understand these associations in other populations. Highlights: Obesity and vitamin D deficiency and insulin resistance are worldwide pandemic problems. Those three affections could be associated but the mechanisms are not well elucidated. Adiponectin was not associated with vitamin D and insulin resistance in eutrophic or people with obesity in Brazil. There are doubts about which variants the relation between them.